Pengaruh Good Corporate Governance terhadap ROA dengan Ukuran Perusahaan sebagai Variabel Mediasi : (Studi Empiris pada Perusahaan Sektor Bahan Baku yang Terdaftar di BEI Periode 2019–2024) - Yulia Minhad; Eddy Suratman; Giriati Giriati (LPPM Universitas Bina Sarana Informatika, 2026)
Selecting appropriate accounting software is a significant challenge for organizations due to diverse functional attributes. Suboptimal choices can adversely affect operational efficiency and financial management quality. This study develops a Decision Support System (DSS) using the Evaluation Based on Distance from Average Solution (EDAS) method to determine the optimal software choice among five alternatives: Zahir, Accurate, Mekari Jurnal, SAP Business One, and Kledo. Data were collected via questionnaires from 30 respondents, including accounting practitioners and active users. The evaluation focused on five key criteria: software pricing, ease of use, feature completeness, system integration, and technical support. The EDAS method evaluated these alternatives by calculating their deviation from the average solution through Positive Distance from Average (PDA) and Negative Distance from Average (NDA), resulting in a final Appraisal Score for ranking. The results show that EDAS produces a clear, discriminative ranking. Zahir achieved the highest score (0.798), followed by Mekari Jurnal (0.779), SAP Business One (0.553), Kledo (0.500), and Accurate (0.444). These findings demonstrate that the EDAS approach effectively supports objective multi-criteria decision-making and possesses strong potential for implementation in digital-based recommendation systems for accounting software selection, ensuring businesses make data-driven, efficient choices.